Sildenafil, a cyclic GMP phosphodiesterase inhibitor, induces microglial modulation after focal ischemia in the neonatal mouse brain. Issue 1 (December 2016) - Moretti, Raffaella; Leger, Pierre-Louis; Besson, Valérie; Csaba, Zsolt; Pansiot, Julien; Di Criscio, Lorena; Gentili, Andrea; Titomanlio, Luigi; Bonnin, Philippe; Baud, Olivier; Charriaut-Marlangue, Christiane
Abstract Background Perinatal ischemic stroke is the most frequent form of cerebral infarction in neonates; however, evidence-based treatments are currently lacking. We have previously demonstrated a beneficial effect of sildenafil citrate, a PDE-5 inhibitor, on stroke lesion size in neonatal rat pups. The present study investigated the effects of sildenafil in a neonatal mouse stroke model on (1) hemodynamic changes and (2) regulation of astrocyte/microglia-mediated neuroinflammation. Methods Ischemia was induced in C57Bl/6 mice on postnatal (P) day 9 by permanent middle cerebral artery occlusion (pMCAo), and followed by either PBS or sildenafil intraperitoneal (i.p.) injections. Blood flow (BF) velocities were measured by ultrasound imaging with sequential Doppler recordings and laser speckle contrast imaging. Animals were euthanized, and brain tissues were obtained at 72 h or 8 days after pMCAo. Expression of M1- and M2-like microglia/macrophage markers were analyzed. Results Although sildenafil (10 mg/kg) treatment potently increased cGMP concentrations, it did not influence early collateral recruitment nor did it reduce mean infarct volumes 72 h after pMCAo. Nevertheless, it provided a significant dose-dependent reduction of mean lesion extent 8 days after pMCAo. Suggesting a mechanism involving modulation of the inflammatory response, sildenafil significantly decreased microglial density at 72 h and 8 days after pMCAo. Gene expression profiles indicated that sildenafil treatment also modulates M1- (ptgs2, CD32 andCD86 ) and M2-like (CD206, Arg-1 andLgals3 ) microglia/macrophages in the late phase after pMCAo. Accordingly, the number of COX-2+ microglia/macrophages significantly increased in the penumbra at 72 h after pMCAo but was significantly decreased 8 days after ischemia in sildenafil-treated animals. Conclusions Our findings argue that anti-inflammatory effects of sildenafil may provide protection against lesion extension in the late phase after pMCAo in neonatal mice. We propose that sildenafil treatment could represent a potential strategy for neonatal ischemic stroke treatment/recovery.